Prostate Cancer: Evidence Based Management Guidelines for Uganda - Kigula Mugambe, J.B.; Watya, S.; Kaggwa, S.; Luutu, I.; Kanyike, D.M.; Luwaga, A.; Fualal, J.; Jombwe, J.; Galukande, M.; Gakwaya, Leng A. (East and Central African Journal of Surgery, 2011)
Cancer of the prostate is now the commonest malignancy in the male in Uganda1 while Kaposi’s sarcoma was the commonest in the 1990’s2. The incidence rate is 39.2:100,000 males in Kyaddondo County and it has been rising in Uganda since 19603. It is a challenging tumour to treat with most of the patients presenting with metastatic disease. Members of the Uganda cancer working group (Appendix I) compiled the currently accepted, most appropriate approach to the management of prostate cancer which was deemed available and accessible. All recommendations were category 2 A unless otherwise stated (Appendix II).
Keywords: Prostate Cancer; Management Guidelines; Uganda